RESEARCH OF DETECTING DEFECTS IN POLYUREA ANTI-CORROSIVE PIPES BY USING ULTRASONIC GUIDED WAVES (MT) - LIANG HaoRan; WU Jing; LIU Feng; ZHENG MingFang; LIU ZhongMing; MA HongWei (Jixie qiangdu)
In recent years, as a new type of anti-corrosion material, polyurea coatings have been widely applied to the protection of internal and external walls for pipes. In order to overcome the shortage of traditional ultrasonic testing with low efficiency, the imagine of detecting some cracks in polyurea anti-corrosive pipes was proposed, which based on ultrasonic guided wave detection technology, and it would be studied by numerical simulation. By analyzing the analytical model in the polyurea anti-corrosion pipes, established the three-dimensional cylindrical model of the viscoelastic-elastic composite material by finite element software Abaqus, and simulated the propagation state in which the L（0,2） modal guided wave with the different excited frequencies. Combined with the study of its dispersion and attenuation for selecting optimize frequency, and the analysis of defect detection for the model were accomplished the simulated. The results of research show that the results of numerical simulation are basically consistent with experimental verification, which show that it is effective to use the ultrasonic guided waves for detecting defects of polyurea anti-corrosion pipes and realizing the location of defects.